PERLINDUNGAN HUKUM TERHADAP KONSUMEN PADA PRODUK OBAT TRADISIONAL YANG BEREDAR DI MASYARAKAT - Dwi Atmoko; Ahmad Baihaki (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Currently, the distribution of traditional medicines is increasingly widespread in society. The various products offered are very varied, ranging from local to international products. As is known, various kinds of diseases arise in society. People from various economic levels, especially from weak economic circles, are better off looking for traditional medicine because the price of the medicine may be expensive and the side effects it causes. Legal protection for the public as regulated in Law Number 8 of 1999 concerning Consumer Protection provides protection for the public regarding products sold by business actors. Business actors who produce traditional medicines are very diverse, ranging from large scale to small scale. Then, along the way, many traditional medicine businesses in making their products sometimes do not heed the regulations made by the government, namely by mixing their herbal products with chemical drugs, which are sometimes very dangerous for consumers who use these products. Basically, traditional medicines are pure plants which are believed to have the efficacy of treating certain diseases, the aim of which is to cure a person's existing disease. Consumer protection for medicines circulating in the community must receive strict supervision from the government, so as not to cause fatalities. Strict regulations on business actors must be monitored comprehensively and continuously. Strict sanctions must be given to business actors who violate the provisions so that it can have a deterrent effect, it is hoped that these business actors will not make the same mistakes, so that consumer protection can be achieved properly and optimally.